Integrative analysis of hub genes and key pathway in two subtypes of diffuse large B‐cell lymphoma by bioinformatics and basic experiments. Issue 11 (21st September 2021) - Li, Qian; Meng, Ye; Hu, Linhui; Charwudzi, Alice; Zhu, Weiwei; Zhai, Zhimin
Abstract: Background: The germinal center B‐cell (GCB) and activated B‐cell (ABC) subtypes of diffuse large B‐cell lymphoma (DLBCL) have a significant difference in prognosis. This study aimed to identify potential hub genes, and key pathways involved in them. Methods: Databases including Gene Expression Omnibus (GEO), Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and STRING were accessed to obtain potential crucial genes and key pathways associated with the GCB and ABC. Then qRT‐PCR and Western blot experiments were performed to verify the most clinically significant gene and pathway. Results: Three cohort datasets from the GEO database were analyzed, including 195 GCB and 169 ABC samples. We identified 1113 differentially expressed genes (DEGs) between the GCB and ABC subtypes. The DEGs were mainly enriched in biological processes (BP). The KEGG analysis showed enrichment in cell cycle and Wnt signaling pathways. We selected the top 10 genes using the STRING database and Cytoscape software. We used 5 calculation methods of the cytoHubba plugin, and found 3 central genes (IL‐10, CD44, CCND2). CCND2 was significantly related to the prognosis of DLBCL patients. Besides, our experimental results demonstrated a significantly higher expression of CCND2 in the ABC‐type cell line than in the GCB‐type; it was proportional to the expression of key proteins in the Wnt signaling pathway. Conclusion: CCND2 overexpression and Wnt pathway activation might be the main reasons for the poor prognosis of ABC‐DLBCL. Abstract : The study revealed that CCND2 overexpression and Wnt pathway activation may be factors of the poor prognosis of ABC‐subtype DLBCL by integrative bioinformatic analysis and basic experiments.